STRATEGIC FRAMEWORK OF HUMAN RESOURCES DEVELOPMENT TO INCREASE PERFORMANCE FOR INTERNAL CUSTOMERS (STUDY AT VOCATIONAL HIGH SCHOOL IN WEST JAVA) - Tresnajaya, Tatan Jaka (EARR (Educational Administration Research and Review), 2017)
Services to internal customers have not been a focus of attention in school. Services to internal customers are not the main priority. These conditions encourage the deficient optimal in vocational education services to external customers. The purpose of research is to identify the strategic framework in the development of human resources development to realize the performance of services for customers Internal. The research is using descriptive type survey. The results showed that teachers and staff received deficient attention. Based on the framework strategy which is owned by the primary focus is fulfill the internal customers need through increased critical awareness and values fundamental individual value commitment to vocational education.